Aggregation control of anionic pentamethine cyanine enabling excitation wavelength selective NIR-II fluorescence imaging-guided photodynamic therapy - Yibin Li; Fei Qu; Fang Wan; Cheng Zhong; Jingyi Rao; Yijing Liu; Zhen Li; Jintao Zhu; Zhong’an Li (Nature Communications)
Abstract Near-infrared (NIR)-II fluorescence imaging-guided photodynamic therapy (PDT) has shown great potential for precise diagnosis and treatment of tumors in deep tissues; however, its performance is severely limited by the undesired aggregation of photosensitizers and the competitive relationship between fluorescence emission and reactive oxygen species (ROS) generation. Herein, we report an example of an anionic pentamethine cyanine (C5T) photosensitizer for high-performance NIR-II fluorescence imaging-guided PDT. Through the counterion engineering approach, a triphenylphosphine cation (Pco) modified with oligoethylene glycol chain is synthesized and adopted as the counterion of C5T, which can effectively suppress the excessive and disordered aggregation of the resulting C5T-Pco by optimizing the dye amphipathicity and enhancing the cyanine-counterion interactions. Dynamic tuning of fluorescence characteristics and ROS generation is achieved at the aggregate level, resulting in an impressive type I ROS generation under 760 nm light irradiation, accompanied by efficient NIR-II fluorescence emission excited at 808 nm. As a result, excitation wavelength selective NIR-II fluorescence imaging-guided PDT has been successfully demonstrated for tumor diagnosis and therapeutics of female mice.